Encouraging effect of Brahmi Ghrita in amnesia - Yadav K.D.; Reddy K.R.C.; Kumar V. (My University, 2025)
Context: Brahmi Ghrita (BG) contains Brahmi (Bacopa monneri), Vacha (Acorus calamus), Kushtha (Saussurea lappa), Shankhapushpi (Convolvulus pluricaulis) and Puran Ghrita, prepared as per sneha paka process. Aim: The aim of this study was to assess the learning and memory activity of BG in Amnesic rats. Materials and Methods: The Learning and memory activity of BG (400 and 800 mg/kg, per oral) was evaluated in scopolamine (1 mg/kg, sub cutaneous) challenged rats, using elevated maze plus, passive avoidance test and active avoidance test. Results: BG treated scopolamine challenged rat demonstrated a significant decrease in transfer latency in modified elevated plus maze test and increase in step through latency in passive avoidance test compared to control rats in a dose dependent manner. BG treated rats took significant less number of total trials, shock trial and total time for jumping into safe compartment. Conclusion: BG antagonises the action of scopolamine.